Core Ethical Values Of Character Education: Based On Islamic Values - Yayan Supian; Aan Hasanah; Bambang Samsul Arifin (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this article is to explore the fundamental ethical principles of character education based on Islamic principles. Islam guides its followers to become the best individuals (khoirun ummat). Character education encompasses a broader scope than moral education, as it not only revolves around distinguishing between right and wrong, but also instilling positive habits that promote a sense of awareness and comprehension among children/students. This, in turn, fosters a sense of responsibility and dedication to incorporate virtuous behavior in their daily lives. The Prophet SAW epitomizes the Islamic teachings conveyed in the Qur'an and the Prophet's hadiths, thereby earning him the moniker "walking al-Qur'an." Islamic teachings on character have been gradually eroding and experiencing moral decay, with Muslims no longer serving as exemplary role models. The research approach utilized is qualitative, with a descriptive analysis method, and the data collection involves reviewing literature and previous studies.